2016
DOI: 10.13005/ojc/320408
|View full text |Cite
|
Sign up to set email alerts
|

Studies on The Synthesis of Fluorinated Schiff Bases; Biological Activity of Resulting (E)-N-Benzylidene-2,3,5,6-Tetrafluoropyridin-4-Amine and 4-Amino-2-Ethoxy-3,5,6-Trifluoropyridine

Abstract: The present work is aimed mainly to synthesize new fluorinated compounds and their biological significance against tested bacteria and fungus. Thus, the 4-amino-2-ethoxy-3,5,6-trifluoropyridine 4 was synthesized by the reaction of 4-amino 2,3,5,6-tetrafluoropyridine 1 with benzaldehyde 2 in EtOH to obtain the pure product as white crystals in 33% yield. The purity of this compound was estimated by TLC technique and microanalysis while its structure was supported by the usual spectroscopic methods such as UV, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Raache et al [ 15 ] have reported the synthesis, structural investigations and preliminary antibacterial activity studies of ( E )-1-phenyl- N -(2,3,5,6-tetrafluoropyridin-4-yl)methanimine ( 1 ) ( Figure 1 ). The synthesis of this aldimine was achieved successfully by reacting equimolar ratios of 4-amino-2,3,5,6-tetrafluoropyridine and benzaldehyde in tetrahydrofuran containing an ethanolic solution of potassium hydroxide for 72 h at ambient temperature.…”
Section: Fluorinated Aldimine-type Schiff Basesmentioning
confidence: 99%
See 2 more Smart Citations
“…Raache et al [ 15 ] have reported the synthesis, structural investigations and preliminary antibacterial activity studies of ( E )-1-phenyl- N -(2,3,5,6-tetrafluoropyridin-4-yl)methanimine ( 1 ) ( Figure 1 ). The synthesis of this aldimine was achieved successfully by reacting equimolar ratios of 4-amino-2,3,5,6-tetrafluoropyridine and benzaldehyde in tetrahydrofuran containing an ethanolic solution of potassium hydroxide for 72 h at ambient temperature.…”
Section: Fluorinated Aldimine-type Schiff Basesmentioning
confidence: 99%
“…Ampicillin—a broad-spectrum aminopenicillin—was used as a standard antibiotic. Tetrafluorinated aldimine 1 at the highest concentration tested (983.5 µM) was shown to reveal moderate activity against both Gram-negative bacteria of clinical interest, considering its zone inhibition sizes in relation to that of ampicillin [ 15 ].…”
Section: Fluorinated Aldimine-type Schiff Basesmentioning
confidence: 99%
See 1 more Smart Citation